Book Review: Technology and forced migration Ukrainian migrants in Central and Eastern Europe - Tétényi, András (Society and Economy in Central and Eastern Europe, 2026)
Technology and Forced Migration – Ukrainian Migrants in Central and Eastern Europe is a timely and highly relevant edited volume that examines the role of information and communication technologies (ICTs) in the migration trajec-tories, decision-making processes, and integration experiences of Ukrainian forced migrants in Central and Eastern Europe (CEE). With a particular focus on the Visegrad Four (V4) countries of Czechia, Hungary, Poland, and Slovakia, the book makes an important contribution to the growing literature on digital migration, forced displacement, and migration governance by situating these debates in a region that has been underexplored in both migration studies and science and technology studies.